Nyale sea worms: A natural approach to diabetes prevention among Mbojo Bima farmers - Nurfahmiatunnisa, Nurfahmiatunnisa; Mallapiang, Fatmawaty; Satrianegara, M. Fais; Damayanti, Dwi Santy; Ismail, Ahmad La Ode; Habibi, Habibi (CORE JOURNAL, 2024)
Mbojo farmers are at high risk of suffering from Diabetes Mellitus (DM) due to hard work and a diet high in carbohydrates. However, the incidence of DM among them is relatively low thanks to the tradition of using the Nyale seaworm (Eunice sicilliensis) for prevention and treatment. This research aims to uncover these traditional practices in Parado District, West Nusa Tenggara, in 2024. The research method used is qualitative with a case study approach. The informants consisted of six people who were selected through purposive sampling. The results of the study showed that DM prevention was carried out by consuming fresh Nyale worms during mass spawning in the Nyale smell tradition. This tradition involves prayer and prayer together, followed by the taking of Nyale on the 9th day of the Hijri month. Treatment is carried out by drying, punching, and applying Nyale to the wound of DM sufferers. These findings show the potential of local traditions as a preventive measure and natural treatment. The implications include the development of DM prevention programs, increasing access to health services, occupational health education, and improving the work environment. Researchers recommend further studies to explore the benefits of Nyale worms as a candidate for diabetes drugs, while supporting the development of natural ingredients in modern medicine